Preditores de sucesso na utilização de pessário vaginal para tratamento de prolapso de órgãos pélvicos após seguimento de um ano - Niigaki, Danielle Ikeda [UNIFESP] (2018)
Objective: To identify factors contributing to successful pessary use for treatment of pelvic organ prolapse for periods longer than one year. Methods: A prospective observational study was performed with 247 women evaluated for symptomatic pelvic organ prolapse at Urogynecology clinic of Universidade Federal de São Paulo (UNIFESP), who accepted the treatment with the pessary during October 2012 to October 2016. We compared the characteristics of those who continued pessary usage for over a year with those who discontinued. The data were analyzed using the following statistical methods: Student's T-test, Wilcoxon Mann-Whitney test, multivariate logistic regression and decision tree. Results: 247 patients tested the pessary, only 236 were included in the analysis; of these, 110 patients (46.6%) continued to use the pessary for more than one year. Through multivariate logistic regression we identified the factors associated to the use of the pessary for periods longer than one year, such as: hysterectomy (OR=3.40, IC: 3.23-3.57, p=0.007). Factors related to the higher odds of discontinued usage are: vulvovaginitis (OR=0.11, IC: 0.10-0.12, p=0.0002), higher parity (OR=0.865, IC: 0.85-0.87, p=0.029) and topic vaginal estrogen use (OR=0.39, IC: 0.38-0.41, p=0.019). The presence of complications with the use of the pessary was not associated with a higher dropout rate (OR = 1.74, CI: 1.69-1.79, p = 0.030). Evaluation was also performed through the decision tree that corroborated with logistic regression findings. Conclusion: The presence of vulvovaginitis was highly predictive of non-success of pessary use. Hysterectomy is a good predictor for long-term use. The presence of complications, with the exception of vulvovaginitis, did not interfere with the withdrawal of long-term treatment. The use of vaginal estrogen was not a good predictor of treatment maintenance. There was improvement in patients' quality of life.